Cross-Border Markets and Their Impacts on Security (A Case Study in Torkham Border) - Janmohammad Miakhil; Shamsurahman Zahid; Enayatullah Dadman (Randwick International of Social Science Journal, 2022)
The concept of security is a concept that encompasses all aspects of human life the aspects that guarantee human life and survival. The realization of security in a geographical environment requires special measures and planning, and it is associated with many issues Such as economical security, political security-military security, social security, health security, environmental security, and so on. There is a parallel and correlation between security and development, which sustainable security focuses on sustainable development at regional, urban, rural even up to the individual levels. Some geographical areas are highly vulnerable from the security side due to their special geographical location, and in recent years there has been an increase in violence and armed conflict, such as borders Afghanistan, the present article seeks to use the field and library methods and seeks to investigate cross border- markets and their impact on the security of areas and on the instability of security. The finding shows that border areas are vulnerable in various aspects of economic, social, and environmental security and face many challenges. To create sustainable security in rural areas and border areas of the provinces, it is necessary to consider the concept of security and rural development strategy to realize a sustainable development